Erythropoietin induces miRNA‐210 by JAK2/STAT5 signaling in PBMCs of End‐stage Renal Disease patients. (6th April 2020) - Felaco, Paolo; Felaco, Mario; Franceschelli, Sara; Ferrone, Alessio; Gatta, Daniela M. P.; Speranza, Lorenza; Patruno, Antonia; De Lutiis, Maria A.; Ballerini, Patrizia; Sirolli, Vittorio; Grilli, Alfredo; Bonomini, Mario; et al.
Abstract : Anemia of chronic kidney disease is associated with blunted response/resistance to erythropoietin‐stimulating agents (ESAs) in hemodialysis (HD) patients. Several molecules have been successfully associated with ESA responsiveness; however, none of them is now considered a valid therapeutic biomarker of erythropoietin resistance in these patients. We performed an evaluation of the level of specific plasma circulating miRNAs in blood samples of HD patients, in relation to ESA treatment, with a follow‐up of 1 year (T0–T3). We found significantly lower circulating levels of all miRNAs analyzed at baseline (T0) in HD patients vs. healthy control (HC). The plasmatic levels of miRNA‐210 resulted significantly and negatively associated with Erythropoietin Resistance Index (ERI), and the variance of ΔmiRNA‐210 (miRNA‐210T3 minus miRNA‐210T0 ) explained significant percentage of ΔERI (ERIT3 minus ERIT0 ) variance. The receiver operating characteristic analysis at T0 showed that the plasmatic level of miRNA‐210 could distinguish HD patients with positive or negative trend in ERI at T3. In vitro, recombinant human erythropoietin (EPO) induced significant release of miRNA‐210 from cultured peripheral blood mononuclear cells, through the activation of Janus kinase 2 (JAK2)/ signal transducer and activator of transcription 5 (STAT5) signaling, but not by the activation of the MAPK protein 38α and extracellular signal‐regulated kinase ½. Accordingly, HD patients with negative ΔERI showed higher level of phosphor‐Janus kinase 2 and nuclear translocation of phosphor‐signal transducer and activator of transcription 5. vs. patients with positive ΔERI or HC. Our data highlighted that chronic HD significantly reduces the circulating level of the miRNAs evaluated; within the targets analyzed, the miRNA‐210 could be considered as a prognostic indicator of ESA responsiveness and index for anemia management. Abstract : Anemia is often associated with resistance to erythropoietin‐stimulating agents in hemodialysis (HD) patients. The plasmatic levels of miRNA‐210 are significantly and negatively associated with erythropoietin resistance in HD and could distinguish the trend in Erythropoietin Resistance Index over time. In vitro, human erythropoietin induced significant release of miRNA‐210 from peripheral blood mononuclear cells, through Janus kinase 2/signal transducer and activator of transcription 5 signaling. The miRNA‐210 could be considered as a prognostic indicator of ESA responsiveness and index for anemia management.